8w+12-6w=5(w+3)-2w

Simple and best practice solution for 8w+12-6w=5(w+3)-2w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8w+12-6w=5(w+3)-2w equation:


Simplifying
8w + 12 + -6w = 5(w + 3) + -2w

Reorder the terms:
12 + 8w + -6w = 5(w + 3) + -2w

Combine like terms: 8w + -6w = 2w
12 + 2w = 5(w + 3) + -2w

Reorder the terms:
12 + 2w = 5(3 + w) + -2w
12 + 2w = (3 * 5 + w * 5) + -2w
12 + 2w = (15 + 5w) + -2w

Combine like terms: 5w + -2w = 3w
12 + 2w = 15 + 3w

Solving
12 + 2w = 15 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
12 + 2w + -3w = 15 + 3w + -3w

Combine like terms: 2w + -3w = -1w
12 + -1w = 15 + 3w + -3w

Combine like terms: 3w + -3w = 0
12 + -1w = 15 + 0
12 + -1w = 15

Add '-12' to each side of the equation.
12 + -12 + -1w = 15 + -12

Combine like terms: 12 + -12 = 0
0 + -1w = 15 + -12
-1w = 15 + -12

Combine like terms: 15 + -12 = 3
-1w = 3

Divide each side by '-1'.
w = -3

Simplifying
w = -3

See similar equations:

| a^2-16a+63=0 | | .5x+4=-6 | | -1+4/25=-1 | | 4x*2c-4+4c=0 | | t(p)=(ln(p/25))/.12 | | 2z+8-9=-30.5 | | m+3-(2)=7 | | .6n+4=18 | | 8x=x-2 | | (-9x-3).2/3 | | r^2-16r+15=0 | | 34x+3+96+59x+75=360 | | 9k+3=12k | | 130+48+14x=360 | | 2w+7=16 | | 42j+19j-18=28 | | 9x-3+30=90 | | n^2-10n-39=0 | | (2x-1)(x+8)=2x^2+15x-8 | | 5sin^2a-5sin^4a=5cos^2a-5cos^4a | | 8+14x-7=7x+56-4x | | Z-7=1+2Z | | 6t=-21 | | 2Y+9=10Y | | 6x+9=rx+t | | x(90-x)=18 | | -22.5=7k-5.5k | | x+60-y-10=180 | | 3=x/-3-1 | | 2*(7/4)^2-7(7/4)-4 | | 15=7x-5(2x+3) | | 39=3(x+2) |

Equations solver categories